2022
DOI: 10.1017/jfm.2022.772
|View full text |Cite
|
Sign up to set email alerts
|

Vortex structures in the wake of a marine propeller operating close to a free surface

Abstract: The present paper analyses the vortical structures in the wake of a naval propeller operating underneath a free surface using detached-eddy simulation. We investigate the flow topology for several loading conditions and compare it with analogous observations behind a propeller operating in open water. We show that the wake topology is similar to that observed in open water only for low-loading conditions. For mild blade loading, the free surface's presence seems to stabilize the flow. On the contrary, for high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The motion of the propeller led to a decrease in the elevation of the propeller free surface, primarily at the downstream centerline of the propeller. As the flow developed downstream, the downward effect of the free surface would spread laterally, and the elevation of the free surface downstream of the centerline of the propeller would rise again, which is consisted with the phenomenon observed in the study by Lungu [38] and Di Mascio et al [39]. The shape of the free surface would undergo periodic fluctuations due to the rotation of the propeller, which was more pronounced under the flat inflow condition.…”
Section: Influence Of Propeller Rotation On Free Surfacesupporting
confidence: 60%
“…The motion of the propeller led to a decrease in the elevation of the propeller free surface, primarily at the downstream centerline of the propeller. As the flow developed downstream, the downward effect of the free surface would spread laterally, and the elevation of the free surface downstream of the centerline of the propeller would rise again, which is consisted with the phenomenon observed in the study by Lungu [38] and Di Mascio et al [39]. The shape of the free surface would undergo periodic fluctuations due to the rotation of the propeller, which was more pronounced under the flat inflow condition.…”
Section: Influence Of Propeller Rotation On Free Surfacesupporting
confidence: 60%
“…To verify the adequacy of the adopted grid far from the aorta surfaces, where the turbulence model reduces to a large-eddy simulation, the modelled kinetic energy was evaluated and compared with the total energy. To do that, we followed Di Mascio et al [40]. Figure 6 shows the ratio between the modelled kinetic energy and the total kinetic energy on various cross-sections of the aorta geometry for a specific temporal instant (during the systolic phase).…”
Section: Convergence and Grid Sensibility Study: Preliminary Discussionmentioning
confidence: 99%
“…DES was employed to contrast the propeller vortex formation under different conditions, using numerical evaluation. Vortex topologies were exposed under different loading conditions, and they demonstrated that the pronounced interference effects led to the premature collapse of the vortex system, thereby preventing the tip vortex pairing process from occurring [27]. In their study, Posa [28] replicated the wake produced at distinct propulsive coefficients based on the LES method.…”
Section: Introductionmentioning
confidence: 99%